Effect of Strength Training on Pain Reduction and Physical Function Improvement in Postoperative Prostate Cancer Patients - Wisnu Guntur Prakoso; Tadi Tadi; Achmad Fauzi; Navy Sealsi Adinda Prisca Marina; Tintin Sukartini (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Nursing has an important role in improving the health and prevention of complications of post-surgical patients. One of the nursing interventions that can be provided is Pelvic Floor Muscle Exercise (Kegel) which aims to strengthen the muscles that support the bladder and intestines, which are often affected after prostate surgery. To systematically explore the effect of strength training on reducing pain and improving physical function in postoperative prostate cancer patients. The method uses a search through 4 major databases namely PubMed, Scopus, Sciencedirect and ProQuest with a range of 5 years from 2020 to 2025. The literature search used keywords namely "strength training", "pain intensity", "physical function", "postoperative prostate cancer". The critical appraisal guidelines of the Joanna Briggs Institute were used for the appraisal review of the journal. Twelve articles were extracted regarding the effect of strength training on reducing pain and improving physical function in postoperative prostate cancer patients. Overall, the articles yielded several findings regarding differences in pain and physical functional ability with different types of strength training implemented using varying duration, frequency and intensity. Strength training has significant benefits in helping postoperative prostate cancer patients. It is effective in reducing pain, especially pelvic pain and pain related to urinary incontinence, as well as improving the physical function of patients Keywords: Pain Intensity, Physical Therapy, Prostate Cancer, Strength Training.